Cooperative Inquiry in Human Ecology: Historical Roots and Future Applications. (March 2014) - Faust, Victoria; Jasper, Cynthia R.; Kaufman, Ariel; Nellis, Margaret J.
<x xml:space="preserve">Abstract</x> Cooperative inquiry (CI) is examined as a method that can be applied to issues addressed within the field of human ecology. CI aligns with foundational and contemporary paradigms of human ecology. Methodologically, it responds to applied, action‐oriented questions through emphasizing participation in one's surroundings as a core strategy for knowledge generation. CI also engages relationship‐based standards for rigor to address issues in community research such as researcher objectivity, power dynamics, and trust building that emerge for complex and contextual questions. The article includes an explanation of recent inquiries into areas such as parenting, leadership, and art in social change and adult learning, and the researchers suggest future inquiries for human ecology.